ANXA1 and ARG2 drive T cell proliferation in ischemia-reperfusion injury: integrated bulk and single-cell transcriptomic analysis - Zheng, Haofeng; He, Kaiming; Wei, Jianchao; Zhou, Wangtianxu; Kong, Zhiyi; Dai, Qingfu; Dong, Jieyi; Luo, Zihuan; Sun, Qiquan (Frontiers in Cell and Developmental Biology, 2025)
Ischemia-reperfusion injury (IRI) represents a common pathophysiological condition and serves as a shared mechanism underlying diverse critical diseases, including acute kidney injury, myocardial infarction, and stroke. T cells are increasingly recognized as central mediators of immune responses during IRI; however, the mechanisms governing their proliferation remain poorly characterized. Herein, an integrative analysis of bulk and single-cell transcriptomic datasets across multiple organ models was performed to investigate the role of T cell proliferation–related genes in IRI. We identified ANXA1 and ARG2 as key IRI-associated genes, both of which exhibited consistent upregulation during the early stages of injury. Immune infiltration analysis demonstrated that ANXA1 expression correlated most strongly with central memory CD4+ T cell infiltration, whereas ARG2 was linked to T helper 17 cell infiltration. Drug prediction and molecular dynamics simulation further identified Hydrocortamate and NS6180 as potential therapeutic agents targeting T cell proliferation. Single-cell RNA sequencing not only confirmed the active involvement of T cells in IRI progression but also highlighted ANXA1 as a particularly prominent regulator. A renal IRI model was also used to further confirm altered T cell activity and differential expression of these key genes in vivo. Collectively, these findings elucidate the molecular mechanisms driving T cell proliferation in IRI, positioning ANXA1 and ARG2 as promising pan-organ IRI biomarkers and therapeutic targets for mitigating tissue damage and promoting repair.